Correlations of MGMT promoter methylation and IDH1 mutations with the clinical prognosis of malignant glioma patients - ZHANG Ning, MA Hui-hui, WANG Fan, LIANG Wei, WANG Yi-chun, WU Bing-shan, LI Qing-xin (Jichu yixue yu linchuang, 2021)
Objective To analyze retrospectively the IDH1 mutation and MGMT promoter methylation of malignant glioma patients and to identify potential relation to clinical situation. Methods Twenty-five patients with glioma who were received treatment from October 2017 to October 2019 were selected; the survival rate was calculated by Kaplan-Meier method and analyzed by Log-Rank test. Results Univariate analysis showed that negative status of MGMT gene promoter methylation(χ2=4.22,P＜0.05) was an important factor affecting the survival rates of patients, and patients with both negative status of MGMT gene promoter methylation and mutation of IDH1 had a significantly prolonged survival(P＜0.05). Conclusions IDH mutation and MGMT promoter methylation status are significantly related to the prognosis of malignant glioma patients.